Followership in action : cases and commentaries - Carsten, Melissa K.; Koonce, Rob; Bligh, Michelle C.; Hurwitz, Marc (Emerald Group Publishing Limited, 2016)
For years, leading management scholars have assumed the contribution of followers is an effect rather than a cause of an organization's success. The 25 case studies and commentaries in Followership in Action from such diverse places as Canada, France, India, Malaysia, the Netherlands, the United Kingdom, and the United States lend further support to this argument. Followership in Action is a highly practical and scholarly book to which leadership scholars, practitioners, and students will actively turn to better understand and apply followership theory to everyday human resource development, management, and leadership contexts. It was written with administrators, coaches, consultants, executives, human resource professionals, academic professors, and support staff fully in mind. As the study of followership further escalates into the global mainstream of leadership studies, this book offers an excellent way to more proactively engage future leaders and followers in issues that they are likely to face in various organizational settings. Its business, education, and government content will appeal to academia, corporations, non-profits, and other enterprises.